BAHASA “MEMINTA IJIN” MAHASISWA DALAM SMS - Iqbal Nurul Azhar (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2010)
The invention of cellular telephone has brought many changes among the society, especially changes that connect with communication and language aspects. By using a cell phone, people can communicate and use language whenever and wherever they are, whether through call, videocall, MMS or SMS facilities. SMS service, as the most service used by people, is limited by the amount of characters. This limitation then creates a new style of language among the society, which is called as the language style of SMS. Unfortunately, because there is no convention about how to shorten the language in SMS, each person has his/her own way to use and shorten the words in SMS. This language style is very interested to be discussed based on linguistic perspective. This article tries to reveal several language style of SMS.